2018
DOI: 10.6002/ect.2016.0299
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Within the limitations related to small sample size, our results argue against an unusually high risk of graft-versus-host disease after simultaneous pancreas-kidney transplant. Collaboration between solid-organ and stem cell transplant investigators can be fruitful and can improve our understanding of the complications that are shared between the 2 fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It usually presents acutely after liver or small bowel transplants although there have been 15 reported cases of GVHD after pancreas transplants alone or in combination with renal transplants. 3,616 The diagnosis of SOT-associated GVHD is challenging, and the management remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It usually presents acutely after liver or small bowel transplants although there have been 15 reported cases of GVHD after pancreas transplants alone or in combination with renal transplants. 3,616 The diagnosis of SOT-associated GVHD is challenging, and the management remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…None of the 7 patients included in the study demonstrated chimerism at either time points, and none ultimately developed GVHD. 6 Although XY FISH and STR PCR-based assays using peripheral blood have been successfully used to diagnose SOT-associated GVHD and are now being used more routinely, the sensitivity and specificity of these modalities to detect chimerism and predict GVHD after SOTs are not well-defined. Consistent with the observations we reported, there have been several other reported instances in which blood-based testing was later inconsistent with tissue-based PCR, FISH, or histopathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations